1979
DOI: 10.1210/jcem-49-4-638
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Thyrotropin Inhibitory Effect of Histamine in Man

Abstract: Because of certain side effects of cimetidine therapy which may be hormonally mediated (e.g. gynecomastia), there has been recent interest in the possible endocrine effects of this H2 histamine receptor-blocking agent used in the treatment of peptic ulcer disease. Accordingly, the effect of chronic cimetidine therapy on anterior pituitary function was examined in 12 adult men with mild peptic ulcer disease. TRH and insulin-hypolycemic stimulation tests were performed by standard methods. Serum for TSH and PRL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

1981
1981
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…Not much more is known about the histaminergic system. In humans, cimetidine, the blocker of the H> histaminic receptors had no effect on either basal or stimulated TSH levels when giv en acutely [21,53,132], while chronic treatment seemed to increase the response to TRH [72]. Feeding histidine defi cient diets to rats to decrease histamine concentration and thus the histaminergic neurotransmission in the brain did not alter TSH levels [47].…”
Section: Other Transmittersmentioning
confidence: 99%
“…Not much more is known about the histaminergic system. In humans, cimetidine, the blocker of the H> histaminic receptors had no effect on either basal or stimulated TSH levels when giv en acutely [21,53,132], while chronic treatment seemed to increase the response to TRH [72]. Feeding histidine defi cient diets to rats to decrease histamine concentration and thus the histaminergic neurotransmission in the brain did not alter TSH levels [47].…”
Section: Other Transmittersmentioning
confidence: 99%
“…The hypothalamic median eminence contains histamine (May et al, 1979) and histamine H2-receptor antagonists modify pituitary hormone secretion. Intravenous cimetidine stimulates prolactin secretion (Carlson & Ippoliti, 1977), but most studies suggest prolonged oral treatment is without effect (Barber & Hoare, 1979;Van Thiel et al, 1979).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Intravenous cimetidine stimulates prolactin secretion (Carlson & Ippoliti, 1977), but most studies suggest prolonged oral treatment is without effect (Barber & Hoare, 1979;Van Thiel et al, 1979). Whether cimetidine influences TSH secretion and circulating thyroid hormone concentrations is unclear (May et al, 1979;Valk et al, 1981;Knigge et al, 1982). Intravenous ranitidine also stimulates prolactin secretion (Knigge et al, 1981) but prolonged oral use does not (Pasquali et al, 1981).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…The effect of an oral dose is more con troversial. Some studies have not reported any effect of cimetidine on PRL levels [May et al, 1979;Nelis and Van de Meene, 1980a;Valk et al, 1981] but others described a slight stimulating effect [Delle Fave et al, 1977;Bohnet et al, 1978;Hugueset al, 1982]. It is of special interest to determine whether or not histamine H2-receptor antagonists en hance PRL secretion since hyperprolactin emia leads to major side effects such as infer tility and sexual dysfunction.…”
Section: Introductionmentioning
confidence: 99%